218k views
0 votes
If s(x) = 2x2 + 3x - 4, and t(x) = x + 4 then s(x) · t(x) =

1 Answer

4 votes

Answer:


\large\boxed{s(x)\cdot t(x)=2x^3+11x^2+8x-16}

Explanation:


s(x)=2x^2+3x-4,\ t(x)=x+4\\\\s(x)\cdot t(x)\\\\\text{use the distributive property:}\ a(b+c)=ab+ac\\\\s(x)\cdot t(x)=(2x^2+3x-4)(x+4)\\\\=(2x^2+3x-4)(x)+(2x^2+3x-4)(4)\\\\=(2x^2)(x)+(3x)(x)+(-4)(x)+(2x^2)(4)+(3x)(4)+(-4)(4)\\\\=2x^3+3x^2-4x+8x^2+12x-16\\\\\text{combine like terms}\\\\=2x^3+(3x^2+8x^2)+(-4x+12x)-16\\\\=2x^3+11x^2+8x-16

User Jeremiahbuddha
by
5.2k points